Peripheral Blood Eosinophil Count as a Predictor of Corticosteroid Resistance in Paediatric Asthma: A Prospective Observational Study - Shravya S. Rao; Karthik Subrahmanya; Vishwas Kadambila (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Background Asthma is one of the most common chronic inflammatory disorders in children and remains a major cause of morbidity worldwide. Although inhaled corticosteroids (ICS) are the cornerstone of long‐term asthma management, a considerable proportion of paediatric patients exhibit reduced responsiveness to corticosteroid therapy, resulting in persistent symptoms, frequent exacerbations, impaired quality of life and increased healthcare utilization. Early identification of children at risk of corticosteroid resistance may facilitate individualized treatment strategies. Peripheral blood eosinophil count is an inexpensive and readily available biomarker of type‐2 airway inflammation and has been proposed as a predictor of asthma severity and therapeutic response. Objectives To evaluate the association between peripheral blood eosinophil count and corticosteroid resistance in children with bronchial asthma and to determine whether eosinophil count can serve as a practical biomarker for predicting corticosteroid responsiveness. Methods A prospective observational study was conducted among 100 children aged 5–15 years with physician‐diagnosed bronchial asthma attending the Department of Paediatrics, Siddaganga Medical College and Research Institute, Tumakuru, India, between January and December 2025. Clinical characteristics, asthma severity, treatment history and absolute eosinophil count (AEC) were recorded. Patients were classified as corticosteroid‐responsive or corticosteroid‐resistant according to predefined clinical response criteria following adequate corticosteroid therapy. Continuous variables were compared using the independent‐samples t test, while categorical variables were analysed using the chi‐square test. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated, and a p value < 0.05 was considered statistically significant. Results Among the 100 enrolled children, 68 (68%) were classified as corticosteroid responsive and 32 (32%) as corticosteroid resistant. The mean absolute eosinophil count was significantly higher among corticosteroid‐resistant children than corticosteroid‐responsive children (596 ± 210 vs. 328 ± 142 cells/μL; mean difference 268 cells/μL; 95% CI: 189–347; p < 0.001). Eosinophilia (AEC ≥ 500 cells/μL) was present in 68.8% of corticosteroid‐resistant patients compared with 26.5% of corticosteroid‐responsive patients. Elevated eosinophil counts were associated with significantly increased odds of corticosteroid resistance (OR 6.1; 95% CI: 2.5–14.8; p < 0.001). Conclusions Peripheral blood eosinophil count is significantly associated with corticosteroid resistance in paediatric asthma. As an inexpensive and widely available laboratory parameter, eosinophil count may assist clinicians in identifying children at increased risk of poor corticosteroid responsiveness and severe disease, thereby supporting personalized treatment strategies and earlier consideration of targeted biologic therapies.